2018
DOI: 10.11604/pamj.2018.29.26.7107
|View full text |Cite
|
Sign up to set email alerts
|

Etats de stress en consultation externe à l’hôpital général de Bangui dans un contexte de conflit arme: étude transversale descriptive

Abstract: Introductiondans les zones de conflit en Afrique les récentes études rapportent des fréquences élevées des états de stress posttraumatiques (ESPT) notamment en milieu communautaire. L'objectif général de cette étude est de contribuer à une meilleure prise en charge des patients confrontés à la violence subséquente au conflit sociopolitique en cours en République centrafricaine.Méthodesil s'agit d'une étude transversale portant sur les dossiers des patients reçus en consultation externe Trauma center de Médecin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…With regards to predictors of distress, a systematic review identified age as an important factor for prevalence of posttraumatic stress disorder (PTSD), with a sharp incline in childhood years-peaking at around 25 years-and a decline after 55 years of age (1). A cross-sectional study of patients in a hospital run by Doctors Without Borders (MSF) in Central African Republic (CAR), found high prevalence rates of PTSD (33%), acute stress (17%), insomnia (63%), anxiety (45%), and depression (41%), and identified rape, female gender and high anxiety and depression as the main predictors of stress (2). A study of East-African conflict survivors found that stigmatization was associated with risk of PTSD and diminished likelihood of spontaneous remission (3).…”
Section: Introductionmentioning
confidence: 99%
“…With regards to predictors of distress, a systematic review identified age as an important factor for prevalence of posttraumatic stress disorder (PTSD), with a sharp incline in childhood years-peaking at around 25 years-and a decline after 55 years of age (1). A cross-sectional study of patients in a hospital run by Doctors Without Borders (MSF) in Central African Republic (CAR), found high prevalence rates of PTSD (33%), acute stress (17%), insomnia (63%), anxiety (45%), and depression (41%), and identified rape, female gender and high anxiety and depression as the main predictors of stress (2). A study of East-African conflict survivors found that stigmatization was associated with risk of PTSD and diminished likelihood of spontaneous remission (3).…”
Section: Introductionmentioning
confidence: 99%
“…Standing out as a particularly debilitating type of violence, rape correlated significantly with high psychological distress prior to MHPSS. This result is consistent with the findings of the recent MSF CAR study (2). The fact that patients who had experienced rape improved as much as average indicates that the intervention in its current form addresses the psychological needs stemming from this type of violence.…”
Section: Rapesupporting
confidence: 90%
“…High levels of post-traumatic stress were associated with increasing age, primary and secondary education level and female gender . While the first two are not consistent with findings of other studies ( 13 , 15 ), the correlation between female gender and increased likelihood of post-traumatic stress disorder (PTSD), including prolonged duration of PTSD, has been shown both in Western ( 16 ) and Africa ( 17 ) populations.…”
Section: Discussionmentioning
confidence: 58%